Political representation in the wake of ethnic violence and post-conflict institutional reform: Comparing views from Rwandan and Burundian citizens - Bert Ingelaere; Réginas Ndayiragije; Marijke Verpoorten (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The lack of political representation often lies at the origin of identity-based violence, and, when not resolved, can re-ignite violence. We study who perceives gains and losses in political representation in Rwanda and Burundi and why. We rely on a quantitative and qualitative analysis of over 700 individual life histories that cover the period 1985-2015. For both countries, we observe a sharp drop in perceived political representation in the run-up to and during violence, and a reversal across ethnicities in its aftermath, when Tutsi feel more represented than Hutu in Rwanda, and Hutu feel more represented than Tutsi in Burundi. We find that the gap in perceived political representation narrows over time in Rwanda as Hutu gradually perceive increases in substantive representation, which is in line with the idea that Tutsi elites in Rwanda who lack 'input legitimacy' maximize policies aiming for 'output legitimacy'. In Burundi, the gap is widening, suggesting that the Burundian regime has failed to give either input or output legitimacy.
Keywords: D72; D74; 330; political representation; violence; Rwanda; Burundi; life histories; legitimacy